IMPLEMENTASI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM PEMBENTUKAN ORIENTASI POLITIK SANTRI DI PESANTREN - Pradipta, Frans Tory Damara (IAI Sunan Giri Trenggalek, 2026)
This study examines the implementation of Pancasila and Civic Education (PPKn) in shaping the political orientation of santri within Islamic boarding schools (pesantren). The study is grounded in the understanding that pesantren function not only as religious educational institutions but also as spaces for cultivating civic awareness and value-based political orientation. This research employs a qualitative approach through literature study and conceptual analysis of educational practices in pesantren. The findings indicate that the implementation of PPKn in pesantren is not limited to formal classroom instruction, but is deeply embedded in the pesantren culture, including the role modeling of kiai, deliberative traditions, and the collective life of santri. Pancasila values are not taught in isolation; rather, they are integrated with Islamic teachings, which contributes to the formation of a moderate, inclusive, and state-oriented political outlook among santri. This reflects the strategic role of pesantren in fostering political literacy grounded in moral and religious values. The study concludes that civic education in pesantren serves as an essential medium for developing political awareness that is not only normative but also practical in social life. Strengthening the integration between Pancasila values and Islamic teachings within pesantren education is therefore crucial in producing santri with mature and responsible political orientations.